Bi Works as a Li Reservoir for Promoting the Fast‐Charging Performance of Phosphorus Anode for Li‐Ion Batteries (Adv. Energy Mater. 19/2022). Issue 19 (19th May 2022) - Zhang, Shaojie; Zhang, Yiming; Zhang, Ziyi; Wang, Huili; Cao, Yu; Zhang, Baoshan; Liu, Xinyi; Mao, Chong; Han, Xinpeng; Gong, Haochen; Yang, Zhanxu; Sun, Jie
Abstract : Li‐Ion Batteries In article number 2103888, Jie Sun and co‐workers report the development of a Bi anode that works as a small Li reservoir for trapping/emitting Li in lithiation/delithiation processes prior to that of the P anode. Nezha, a protection deity in Chinese folk religion, defeated the Dragon King who caused the flood. Similarly, Bi promotes fast and uniform lithiation/delithiation reactions and avoids continuous cracking of the Bi‐P/C electrode.